How community organizations moderate the effect of armed conflict on migration in Nepal - Williams, Nathalie E. (2013)
This article describes an analytical study of systematic micro-level variability in migration during conflict. The study is based on a multi-dimensional model of individual out-migration that examines the economic, social, and political consequences of conflict and how community organizations condition the experience of these consequences and systematically alter migration patterns. A unique combination of detailed data on violent events and individual behaviours during the Maoist insurrection in Nepal and multi-level event-history models were used to empirically test the model. Results indicate that community organizations dampened the effect of conflict on out-migration by providing resources that helped people to cope with the danger as well as economic, social and political consequences of conflict. This evidence suggests a systematic redistribution of population, partially contingent upon specific resources available in each community, which will likely affect the socio-demographic context of post-conflict Nepal into the future.